2021
DOI: 10.3390/healthcare9070851
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polarized Training on the Athletic Performance of Male and Female Cross-Country Skiers during the General Preparation Period

Abstract: This study aimed to analyze the effect of 12 weeks of polarized training on body composition, cardiorespiratory function, and upper-body power of male and female cross-country skiers during the general preparation period. A total of 16 national cross-country skiers (8 male and 8 female; 8 national cross-country skiers and 8 national biathlon athletes) participated. Polarization training was conducted for 12 weeks from May to July in 2019 during the general preparation period for cross-country skiers. The low-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…In particular, it will be interesting to compare the effects of HIIT training for athletes involved in winter sports, such as skiing, with athletes participating in summer sports. Although there are positive results of HIIT training on skiers [ 45 , 46 ], whether running or bicycle-based HIIT translates into good performance in skiing with a sliding pattern needs further examination. Moreover, it remains unknown how long the HIIT effect lasts after 4 weeks of training.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it will be interesting to compare the effects of HIIT training for athletes involved in winter sports, such as skiing, with athletes participating in summer sports. Although there are positive results of HIIT training on skiers [ 45 , 46 ], whether running or bicycle-based HIIT translates into good performance in skiing with a sliding pattern needs further examination. Moreover, it remains unknown how long the HIIT effect lasts after 4 weeks of training.…”
Section: Discussionmentioning
confidence: 99%
“…Analysing data from previous studies, we observed that weekly aerobic exercise included a combination of high exercise volumes at moderate intensity (i.e., 70–94% of weekly exercise) and low exercise volumes at high intensity (i.e., 6–28% of weekly exercise). 31 , 32 , 33 In addition, studies on athletes have suggested that a combination of moderate- (i.e., ∼70–80% of total training volume) 35 and high-intensity training (i.e., ∼20–30% of total training volume) 35 provides greater improvements in body composition 36 and endurance performance-related variables (e.g., V’O 2 max and lactate thresholds) 37 , 38 than HIIT or MICT alone. To date, to our knowledge, no studies on individuals with obesity have used a priori percentages of MICT and HIIT during weekly training to optimize cardiorespiratory function and the fat oxidation rate during walking or running.…”
Section: Introductionmentioning
confidence: 99%
“…HR can be used to objectively evaluate exercise fatigue and is the easiest indicator to use to assess the intensity of current exercise and exercise fatigue [ 29 ]. Exercise fatigue leads to a decrease in the HR regulation function, HR increases with fatigue and HR is dynamic during exercise.…”
Section: Methodsmentioning
confidence: 99%